Halogen-free rubber conveying belt rubber material and preparation method thereof
By optimizing the formula of halogen-free rubber conveyor belt materials, combining natural rubber, styrene butadiene rubber and butadiene rubber, using a variety of halogen-free flame retardants and fillers, the problem of easy damage to rubber conveyor belts in the metallurgical industry has been solved, and the improvement has been achieved High high temperature and wear resistance, extend service life and reduce costs.
Patent Information
- Application Number
- CN202411427434.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-14
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solder, and more specifically, to a halogen-free rubber conveyor belt compound and a preparation method thereof. Background Art
[0002] Rubber conveyor belt is an important industrial product. As the main component of belt conveyor, it is widely used in modern production and transportation. Rubber conveyor belt is mainly used for large-scale continuous transportation in coal, mining, metallurgy, chemical industry, construction and transportation.
[0003] Among them, the slag of many blast furnaces in the metallurgical industry is directly placed on the conveyor belt. The temperature is very high and it carries sparks, which can easily cause the conveyor belt to melt, break, burn, etc., seriously affecting the service life of the conveyor belt. Therefore, how to improve the high temperature resistance of the conveyor belt and extend the service life of the conveyor belt is an urgent problem to be solved. Summary of the invention
[0004] In order to improve the defects of high solder cost, poor processing performance and anti-oxidation performance, the present application provides a halogen-free rubber conveyor belt compound and a preparation method thereof.
[0005] The present application provides a halogen-free rubber conveyor belt material, which adopts the following technical solution:
[0006] In a first aspect, the present application provides a halogen-free rubber conveyor belt compound, comprising the following raw materials in parts by weight:
[0007] Natural rubber 15-25 parts;
[0008] 40-60 parts of styrene-butadiene rubber;
[0009] 25-35 parts of butadiene rubber;
[0010] 50-100 parts of halogen-free flame retardant;
[0011] 50-80 parts of filler;
[0012] 2-5 parts of vulcanizing agent;
[0013] 5-15 parts of additives;
[0014] The halogen-free flame retardant comprises ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl isooctyl phosphate.
[0015] By adopting the above technical scheme, since natural rubber has excellent comprehensive properties, styrene-butadiene rubber has excellent low rolling resistance and wear resistance; cis-butadiene rubber has the advantages of elasticity, good wear resistance, excellent low-temperature resistance, flex resistance and low heat generation, etc., therefore, the present application preferably adopts natural rubber, styrene-butadiene rubber and cis-butadiene rubber as the rubber base material, which can obtain a rubber with excellent mechanical properties and excellent heat resistance.
[0016] The present application preferably adopts ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl isooctyl phosphate as halogen-free flame retardants. By compounding metal hydroxides, phosphorus-nitrogen flame retardants, silicon flame retardants, intumescent flame retardants, nano-composite materials, etc. as halogen-free flame retardants, the rubber material can obtain a relatively excellent high temperature resistant flame retardant effect.
[0017] Optionally, the mass ratio of the ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl isooctyl phosphate is 12:16:8:9:14:8-10.
[0018] By adopting the above technical scheme, the ratio between the components in the halogen-free flame retardant is optimized in this scheme. Under the appropriate ratio, a relatively good synergistic effect can be generated between the various types of flame retardants, further improving the heat-resistant flame retardant effect of the rubber compound. At the same time, two inorganic flame retardants, magnesium hydroxide and zinc borate, are preferably used in this application. Magnesium hydroxide can replace part of the zinc borate, reduce the amount of zinc borate used, and reduce the cost of the rubber compound. The mass ratio between magnesium hydroxide and zinc borate is optimized to maintain the heat-resistant flame retardant effect of the rubber compound.
[0019] Optionally, the magnesium hydroxide has a hexagonal flake structure.
[0020] By adopting the above technical scheme, magnesium hydroxide with a hexagonal flake structure is preferably used as a flame retardant. The magnesium hydroxide with a hexagonal flake structure has a regular morphology, uniform particle size distribution, and a low specific surface area, so that the magnesium hydroxide can be evenly dispersed in the rubber material, and can form magnesium oxide with a large specific surface area when decomposed, which can improve the adsorption effect of the flame retardant on smoke, further reduce smoke emissions, and improve the flame retardant effect of the rubber material.
[0021] Optionally, the magnesium hydroxide is prepared as follows: adding magnesium chloride solution and ammonia water into a container, stirring and mixing, adding PEG-8000, stirring, high pressure sealing and reacting, collecting precipitates, washing, and drying to obtain magnesium hydroxide with a hexagonal sheet structure.
[0022] By adopting the above technical solution, the preparation process of magnesium hydroxide is optimized, and PEG-8000 is used as a structure-directing agent to obtain hexagonal flake magnesium hydroxide with high crystallinity and regular shape.
[0023] Optionally, the magnesium hydroxide is magnesium hydroxide modified by sodium oleate.
[0024] By adopting the above technical solution, magnesium hydroxide is modified by sodium oleate, and sodium oleate can hydrolyze C 17 H 33C OO - , and stably adsorbed on the surface of magnesium hydroxide, changing the hydrophilicity of magnesium hydroxide to hydrophobicity, that is, further reducing the surface polarity of magnesium hydroxide, improving the dispersion effect of magnesium hydroxide in the rubber, so that magnesium hydroxide can effectively replace zinc borate and play a suitable flame retardant effect.
[0025] Optionally, the filler includes carbon black, basalt fiber, attapulgite and polytetrafluoroethylene.
[0026] By adopting the above technical solution, it is preferred to use materials with different structures such as carbon black, basalt fiber, attapulgite, etc. as fillers. The carbon black is a spherical or flaky structure, the basalt fiber is a long fiber structure, and the attapulgite is a short fiber structure. Therefore, the filler can form a staggered filler network structure in the rubber compound, and the fiber structure can carry out appropriate physical load on the carbon black, which can reduce the agglomeration of the carbon black and make the filler obtain better dispersion. The addition of polytetrafluoroethylene can wrap and lubricate the filler, improve the dispersion of the filler, and make the rubber compound obtain uniform strength; at the same time, during the friction process, the polytetrafluoroethylene powder can also cover the wear surface to form a lubricating layer, thereby improving the hydrophobicity and wear resistance of the rubber compound.
[0027] Optionally, the carbon black is ozone-modified carbon black.
[0028] By adopting the above technical scheme and using ozone to modify carbon black, the oxygen-containing functional groups on the surface of carbon black can be increased, the surface free energy of carbon black can be increased, the bonding effect between carbon black and natural rubber can be improved, and the construction of the filler network in the filler can be promoted, which can effectively improve the mechanical strength and wear resistance of the rubber.
[0029] Optionally, the attapulgite is attapulgite modified with phenolic resin.
[0030] By adopting the above technical scheme, the attapulgite is modified by phenolic resin, and the phenolic hydroxyl groups in the phenolic resin can react with active groups such as silanol groups in the attapulgite to form an organic-inorganic hybrid network, which can be combined with the basalt fibers in the filler to form a complex filler network. After the filler is added to the rubber, a complex network structure in which the resin network and the rubber network are interwoven and interpenetrated can be formed, which can effectively improve the mechanical properties and wear resistance of the rubber, thereby extending the service life of the rubber.
[0031] Optionally, the basalt fiber is loaded with glass microbeads or corundum.
[0032] By adopting the above technical solution, after glass microbeads are loaded on basalt fibers, the bonding effect between basalt fibers and rubber can be improved. After the regular spherical structure is introduced, the possibility of filler agglomeration is further reduced, so that the filler is evenly dispersed in the rubber and the transportation resistance of the rubber can be reduced. Diamond abrasive has multiple layers of spheres, which can cooperate with carbon black to form a tighter rubber network structure, which can effectively improve the mechanical properties of the rubber. Diamond abrasive can also cooperate with polytetrafluoroethylene to improve the hydrophobicity of the rubber.
[0033] In a second aspect, the present application provides a method for preparing a halogen-free rubber conveyor belt compound, using the following technical solution:
[0034] A method for preparing a halogen-free rubber conveyor belt compound comprises the following steps:
[0035] S1. Raw material preparation: take natural rubber, styrene-butadiene rubber, butadiene rubber, halogen-free flame retardant, filler, vulcanizing agent and additives respectively by weight;
[0036] S2. Preparation of rubber compound: firstly, natural rubber is placed in an internal mixer for internal mixing to obtain plasticized rubber; plasticized rubber, styrene-butadiene rubber and cis-1,2-butadiene rubber are placed in an internal mixer for mixing, and auxiliary agents and fillers are added to the internal mixer, and mixing is continued, and flame retardants and vulcanizing agents are added, and sheets are produced, and the mixture is cooled to obtain rubber compound.
[0037] In summary, this application has the following beneficial effects:
[0038] 1. Since the present application preferably adopts ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl isooctyl phosphate as halogen-free flame retardants, and metal hydroxides, phosphorus-nitrogen flame retardants, silicon flame retardants, intumescent flame retardants, nano-composite materials, etc. are compounded as halogen-free flame retardants, the rubber material can obtain a relatively excellent high temperature resistant flame retardant effect.
[0039] 2. In the present application, magnesium hydroxide with a hexagonal flake structure is preferably used as a flame retardant. The hexagonal flake structure of magnesium hydroxide has a regular morphology, uniform particle size distribution, and a low specific surface area, so that the magnesium hydroxide can be evenly dispersed in the rubber compound, and can form magnesium oxide with a large specific surface area when decomposed, which can improve the adsorption effect of the flame retardant on smoke, further reduce smoke emissions, and improve the flame retardant effect of the rubber compound.
[0040] 3. The filler in the present application can form an interlaced filler network structure in the rubber, and the fiber structure can carry out appropriate physical load on carbon black, reduce the agglomeration of carbon black, and make the filler obtain better dispersion. The addition of polytetrafluoroethylene can wrap and lubricate the filler, improve the dispersion of the filler, and make the rubber obtain uniform strength; at the same time, during the friction process, the polytetrafluoroethylene powder can also cover the wear surface to form a lubricating layer, thereby improving the hydrophobicity and wear resistance of the rubber. DETAILED DESCRIPTION
[0041] The present application is further described in detail below with reference to the embodiments.
[0042] Preparation Example
[0043] Preparation Example of Magnesium Hydroxide
[0044] Preparation Example 1
[0045] Add 1 mol / L magnesium chloride solution and 1 mol / L ammonia water into a container, stir and mix for 10 minutes, add PEG-8000 in an amount of 3%, stir, transfer to an autoclave, and react at 120°C under high pressure and sealed condition for 12 hours. Collect the precipitate, wash it, and dry it at 80°C for 6 hours to obtain magnesium hydroxide with a hexagonal flake structure.
[0046] Preparation Example 2
[0047] Add 1 mol / L magnesium chloride solution and 1 mol / L ammonia water into a container, stir and mix for 10 minutes, add PEG-600 in an amount of 3%, stir, transfer to an autoclave, and react at 120°C under high pressure and sealed for 12 hours. Collect the precipitate, wash, and dry at 80°C for 6 hours to obtain magnesium hydroxide with a hexagonal flake structure.
[0048] Preparation Example 3
[0049] Weigh 5.0 g of the Mg(OH)2 powder prepared in Preparation Example 1, add water to prepare a slurry with a mass fraction of 3%, transfer it to a container and stir it, and after it is evenly mixed, add 3% sodium oleate in a water bath to react. After the reaction is completed, naturally cool to room temperature, wash with distilled water 3 times, and then dry it in a vacuum drying oven at 80°C for 6 hours to obtain modified magnesium hydroxide.
[0050] Carbon black preparation example
[0051] Preparation Example 4
[0052] The carbon black was placed in a wide-mouth bottle with a rubber stopper, and ozone was introduced to treat the carbon black. The gas flow rate of the ozone generator was 5 L / min-1, the mass concentration was 60 mg·L-1, and the treatment time was 72 h. Ozone-modified carbon black was obtained.
[0053] Attapulgite Preparation Example
[0054] Preparation Example 5
[0055] Add phenol to a container, heat to 50°C until the phenol melts, add oxalic acid to adjust the pH to 1, add formaldehyde dropwise under reflux (the molar ratio of phenol to formaldehyde is 1), and reflux at 100°C. After the reflux, add an aqueous solution containing attapulgite, continue stirring, and perform vacuum distillation at 150°C and -0.5MPa to stop the reaction and obtain hybrid attapulgite. The mass ratio of phenolic resin to attapulgite is 10:1.
[0056] Basalt fiber preparation example
[0057] Preparation Example 6
[0058] Mix 10% KH550 with anhydrous ethanol to obtain a mixed solution, adjust the pH of the mixed solution to 4-5, add glass beads (solid-liquid ratio of 1:5) to the mixed solution, stir for 2 hours, filter, wash, and dry to obtain modified glass beads. Mix the modified glass beads with epoxy resin at a mass ratio of 1:1 to obtain epoxy-modified glass beads, mix the epoxy-modified glass beads with basalt fibers, stir and disperse, filter, dry, oscillate, separate, and crush to obtain modified basalt fibers.
[0059] Preparation Example 7
[0060] Mix 10% KH550 with anhydrous ethanol to obtain a mixed solution, adjust the pH of the mixed solution to 4-5, add corundum (solid-liquid ratio is 1:5) to the mixed solution, stir for 2 hours, filter, wash, and dry to obtain modified corundum. Mix the modified corundum with epoxy resin in a mass ratio of 1:1 to obtain epoxy modified corundum, mix the epoxy modified corundum with basalt fiber, stir and disperse, filter, dry, oscillate, separate, and crush to obtain modified basalt fiber.
[0061] Example
[0062] Examples 1-3
[0063] On the one hand, the present application provides a halogen-free rubber conveyor belt compound, including natural rubber, styrene-butadiene rubber, butadiene rubber, halogen-free flame retardant, filler, vulcanizer and additives, and the specific quality is shown in the table below.
[0064] Among them, the styrene butadiene rubber is solution polymerized styrene butadiene rubber.
[0065] The halogen-free flame retardant includes ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl ethyl phosphate in a mass ratio of 12:16:8:9:14:8.
[0066] The filler comprises carbon black, basalt fiber, attapulgite and polytetrafluoroethylene in equal weight ratio.
[0067] The vulcanizing agent includes lanthanum cerium sulfide and sulfur in a mass ratio of 1:4.
[0068] The additives include antioxidant RD, accelerator CZ, protective wax, anti-scorch agent CTP, accelerator TMTD and antioxidant 4020 in equal mass ratio.
[0069] On the other hand, the present application provides a method for preparing a halogen-free rubber conveyor belt compound, comprising the following steps:
[0070] S1. Raw material preparation: take natural rubber, styrene-butadiene rubber, butadiene rubber, halogen-free flame retardant, filler, vulcanizing agent and additives respectively by weight;
[0071] S2. Preparation of rubber compound: firstly place natural rubber in an internal mixer and mix it at 40 rpm for 3 min to obtain plasticized rubber; put plasticized rubber, styrene-butadiene rubber and butadiene rubber into an internal mixer and mix them at 50 rpm for 1 min, add additives and fillers into the internal mixer and continue mixing for 3 min, discharge the rubber at 140°C, add flame retardant and vulcanizing agent, stir at 450 rpm for 3 min, discharge the rubber at 100°C, take out sheets, cool and stand for 8 h to obtain rubber compound.
[0072] Table 1 Composition of Examples 1-3
[0073] Weight / kg Example 1 Example 2 Example 3 Natural rubber 15 20 25 Styrene Butadiene Rubber 60 50 40 Butadiene rubber 25 30 35 Halogen-free flame retardant 60 80 100 filler 50 65 80 Vulcanizing agent 2 3 5 Additives 5 10 15
[0074] Example 4
[0075] The difference from Example 2 is that the halogen-free flame retardant includes ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl ethyl phosphate in a mass ratio of 12:16:8:9:14:10.
[0076] Example 5
[0077] The difference from Example 2 is that the halogen-free flame retardant includes ammonium polyphosphate in a mass ratio of 12:16:8:9:14:8, magnesium hydroxide prepared in Preparation Example 1, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl ethyl phosphate.
[0078] Example 6
[0079] The difference from Example 2 is that the halogen-free flame retardant includes ammonium polyphosphate in a mass ratio of 12:16:8:9:14:10, magnesium hydroxide prepared in Preparation Example 2, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl ethyl phosphate.
[0080] Example 7
[0081] The difference from Example 2 is that the halogen-free flame retardant includes ammonium polyphosphate in a mass ratio of 12:16:8:9:14:10, magnesium hydroxide prepared in Preparation Example 3, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl ethyl phosphate.
[0082] Example 8
[0083] The difference from Example 2 is that the filler includes the carbon black, basalt fiber, attapulgite and polytetrafluoroethylene prepared in Preparation Example 4 in equal mass ratios.
[0084] Example 9
[0085] The difference from Example 2 is that the filler includes the carbon black prepared in Preparation Example 4, basalt fiber, attapulgite prepared in Preparation Example 5 and polytetrafluoroethylene in equal mass ratios.
[0086] Example 10
[0087] The difference from Example 2 is that the filler includes the carbon black prepared in Preparation Example 4, the basalt fiber prepared in Preparation Example 6, the attapulgite prepared in Preparation Example 5 and polytetrafluoroethylene in equal mass ratios.
[0088] Embodiment 11
[0089] The difference from Example 2 is that the filler includes the carbon black prepared in Preparation Example 4, the basalt fiber prepared in Preparation Example 7, the attapulgite prepared in Preparation Example 5 and polytetrafluoroethylene in equal mass ratios.
[0090] Comparative Example
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 2 is that only ammonium polyphosphate is used as the halogen-free flame retardant in this comparative example.
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 2 is that magnesium hydroxide is not added to the halogen-free flame retardant in this comparative example.
[0095] Performance testing
[0096] (1) High temperature resistance test: Use GT-7017 high temperature aging test chamber to test the tensile properties of the rubber compound according to GB / T3512-2014 "Hot air accelerated aging and heat resistance test for vulcanized rubber or thermoplastic rubber". The heat treatment is 180℃ for 168h.
[0097] (2) Flame retardant performance test: According to ASTM D2863-2000 standard, LOI (Limiting Oxygen Index, the minimum percentage of oxygen required to maintain the combustion of the sample material in a nitrogen and oxygen mixture, used to characterize the flame retardant effect of the flame retardant) was measured using an HC-2 oxygen index meter (Nanjing Jiangning Analytical Instrument Factory). The sample size was 140 mm × 6 mm × 3 mm.
[0098] (3) Wear resistance test: A wear test was conducted using a MH-74 DIN abrasion tester in accordance with GB / T9867-2008. Three samples were tested and the average value was taken.
[0099] Table 2 Performance test
[0100]
[0101]
[0102] Combining the performance test comparison in Table 2, we can find that:
[0103] 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the high temperature resistance, flame retardancy and wear resistance of the rubber obtained in Examples 1-3 are all improved, which means that in the present application, by compounding metal hydroxides, phosphorus nitrogen flame retardants, silicon flame retardants, intumescent flame retardants, nanocomposites and the like as halogen-free flame retardants, the rubber can obtain a relatively excellent high temperature resistance and flame retardancy effect. The filler can form an interlaced filler network structure in the rubber, and the fiber structure can carry out a suitable physical load on the carbon black, which can reduce the agglomeration of the carbon black and obtain better dispersion of the filler. The addition of polytetrafluoroethylene can wrap and lubricate the filler, improve the dispersion of the filler, and make the rubber obtain uniform strength; at the same time, during the friction process, the polytetrafluoroethylene powder can also cover the wear surface to form a lubricating layer, thereby improving the hydrophobicity and wear resistance of the rubber.
[0104] 2. By comparing Example 4 with Example 2, it can be found that the high temperature resistance, flame retardancy and wear resistance of the rubber prepared in Example 4 are all reduced, which means that the ratio between the components in the halogen-free flame retardant is optimized in the present application. Under the appropriate ratio, the various types of flame retardants can produce a relatively good synergistic effect, further improving the heat resistance and flame retardancy of the rubber.
[0105] 3. By comparing Examples 5-6 with Example 2, it can be found that the tensile strength, high temperature resistance, flame retardancy and wear resistance of the rubber obtained in Examples 5-6 are all improved, which shows that the magnesium hydroxide with a hexagonal sheet structure is used as a flame retardant in this application. The magnesium hydroxide with a hexagonal sheet structure has a regular morphology, uniform particle size distribution, and a low specific surface area, so that the magnesium hydroxide can be evenly dispersed in the rubber, and can form magnesium oxide with a large specific surface area when decomposed, which can improve the adsorption effect of the flame retardant on smoke, further reduce smoke emissions, and improve the flame retardant effect of the rubber. Selecting PEG-8000 as a structure directing agent can obtain hexagonal sheet-shaped magnesium hydroxide with high crystallinity and regular shape.
[0106] 4. By comparing Example 7 with Example 2, it can be found that the tensile strength, high temperature resistance, flame retardancy and wear resistance of the rubber material prepared in Example 7 are all improved, which indicates that in the present application, sodium oleate is used to modify magnesium hydroxide, and sodium oleate can hydrolyze C in aqueous solution. 17 H 33C OO - , and stably adsorbed on the surface of magnesium hydroxide, changing the hydrophilicity of magnesium hydroxide to hydrophobicity, that is, further reducing the surface polarity of magnesium hydroxide, improving the dispersion effect of magnesium hydroxide in the rubber, so that magnesium hydroxide can effectively replace zinc borate and play a suitable flame retardant effect.
[0107] 5. By comparing Example 8 with Example 2, it can be found that the tensile strength, high temperature resistance, flame retardancy and wear resistance of the rubber prepared in Example 7 are all improved, which means that the ozone treatment in the present application increases the oxygen-containing functional groups on the surface of carbon black, increases the surface free energy of carbon black, improves the bonding effect between carbon black and rubber, and promotes the construction of the filler network in the filler, which can effectively improve the mechanical strength and wear resistance of the rubber.
[0108] 6. By comparing Example 9 with Example 2, it can be found that the tensile strength, high temperature resistance, flame retardancy and wear resistance of the rubber prepared in Example 9 are improved, which means that the phenolic resin in the present application can form an organic-inorganic hybrid network with attapulgite, and can cooperate with the basalt fiber in the filler to form a complex filler network. After the filler is added to the rubber, a complex network structure of interweaving and interpenetrating resin network and rubber network can be formed, which can effectively improve the mechanical properties and wear resistance of the rubber.
[0109] 7. By comparing Examples 10-11 with Example 2, it can be found that the tensile strength, high temperature resistance, flame retardancy and wear resistance of the rubber prepared in Example 10 are all improved, which shows that after the glass microspheres are loaded on the basalt fibers in the present application, the bonding effect between the basalt fibers and the rubber can be improved, and after the regular spherical structure is introduced, the possibility of filler agglomeration is further reduced, so that the filler is evenly dispersed in the rubber and the transportation resistance of the rubber can be reduced. The corundum has multiple layers of spheres, which can cooperate with carbon black to form a tighter rubber network structure, which can effectively improve the mechanical properties and wear resistance of the rubber.
[0110] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A halogen-free rubber conveyor belt compound, characterized in that: It includes the following raw materials in parts by weight: Natural rubber 15-25 parts; 40-60 parts of styrene-butadiene rubber; 25-35 parts of butadiene rubber; 50-100 parts of halogen-free flame retardant; 50-80 parts of filler; 2-5 parts of vulcanizing agent; 5-15 parts of additives; The halogen-free flame retardant comprises ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl isooctyl phosphate.
2. The halogen-free rubber conveyor belt material according to claim 1, characterized in that: The mass ratio of the ammonium polyphosphate, magnesium hydroxide, zinc borate, melamine phosphate, flame retardant MB202 and diphenyl isooctyl phosphate is 12:16:8:9:14:8-10.
3. The halogen-free rubber conveyor belt material according to claim 2, characterized in that: The magnesium hydroxide is a hexagonal flake structure.
4. The halogen-free rubber conveyor belt material according to claim 3, characterized in that: The magnesium hydroxide is prepared as follows: adding magnesium chloride solution and ammonia water into a container, stirring and mixing, adding PEG-8000, stirring, high pressure sealing and reacting, collecting precipitates, washing, and drying to obtain magnesium hydroxide with a hexagonal sheet structure.
5. The halogen-free rubber conveyor belt material according to claim 2, characterized in that: The magnesium hydroxide is magnesium hydroxide modified by sodium oleate.
6. The halogen-free rubber conveyor belt material according to claim 1, characterized in that: The filler includes carbon black, basalt fiber, attapulgite and polytetrafluoroethylene.
7. The halogen-free rubber conveyor belt material according to claim 6, characterized in that: The carbon black is ozone-modified carbon black.
8. The halogen-free rubber conveyor belt material according to claim 6, characterized in that: The attapulgite is attapulgite modified by phenolic resin.
9. The halogen-free rubber conveyor belt material according to claim 6, characterized in that: The basalt fiber is loaded with glass micro beads or corundum.
10. The method for preparing a halogen-free rubber conveyor belt compound according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Raw material preparation: take natural rubber, styrene-butadiene rubber, butadiene rubber, halogen-free flame retardant, filler, vulcanizing agent and additives respectively by weight; S2. Preparation of rubber compound: firstly, natural rubber is placed in an internal mixer for internal mixing to obtain plasticized rubber; plasticized rubber, styrene-butadiene rubber and cis-1,2-butadiene rubber are placed in an internal mixer for mixing, and auxiliary agents and fillers are added to the internal mixer, and mixing is continued, and flame retardants and vulcanizing agents are added, and sheets are produced, and the mixture is cooled to obtain rubber compound.
Citation Information
Patent Citations
Method for preparing high-dispersion magnesium hydroxide combustion inhibitor with one-step hydrothermal method
CN101269827A
Rubber coating and preparation method thereof
CN104098809A
Ethylene propylene diene terpolymer low-smoke zero-halogen flame retardant soft rubber
CN106674768A
Method for preparing NANO attapulgite and phenolic aerogel and method for preparing abrasion-resistant vehicle tire
US20220251323A1
Cited By
Halogen-free rubber conveying belt and preparation process thereof
CN120173316A